Early Disseminated Lyme Disease with Carditis Complicated by Posttreatment Lyme Disease Syndrome - Cheryl Novak; Andrew Harrison; John Aucott (Case Reports in Infectious Diseases)
Lyme disease is an infectious disease caused by the bacterium Borrelia burgdorferi. When untreated, infection may spread to the heart, nervous system, and joints. Cardiac involvement usually manifests as abnormalities of the conduction system and bradycardia. Treatment of Lyme disease is generally effective, with a subset of patients experiencing persistent, sometimes long-term symptoms called posttreatment Lyme disease syndrome.